Activities of Newer Quinolones against Escherichia coli and Klebsiella pneumoniae Containing the Plasmid-Mediated Quinolone Resistance Determinant qnr - Wang, Minggui (American Society for Microbiology, 2004)
Seventeen qnr-containing transconjugants were constructed with azide-resistant Escherichia coli J53 as the recipient, and the MICs of 12 quinolones were tested by agar dilution methods. Sitafloxacin, BAYy3118, and premafloxacin had higher activity in vitro than ciprofloxacin against transconjugants and donors containing qnr. The donors had higher quinolone MICs than the transconjugants.